Serum Uric Acid Is Independently Associated with Risk of Obstructive Sleep Apnea-Hypopnea Syndrome in Chinese Patients with Type 2 Diabetes. (3rd April 2019) - Zheng, Caiyu; Song, Haiqu; Wang, Shunhua; Liu, Jing; Lin, Tingting; Du, Chunmin; Xie, Huan; Chen, Zhongyun; Zheng, Silan; Li, Zhibin; Li, Xuejun; Liu, Changqin
Abstract : Purpose . We aimed to investigate the association between serum uric acid (SUA) levels and obstructive sleep apnea-hypopnea syndrome (OSAHS) in patients with type 2 diabetes. Methods . A cross-sectional study of 212 type 2 diabetes mellitus (T2DM) patients was conducted in Xiamen, China. All patients underwent polysomnography (PSG) recordings for OSAHS diagnosis. Patients were grouped according to the apnea-hypopnea index (AHI) as mild (5-14.9), moderate (15-29.9), and severe (≧30) OSAHS. Patients withAHI ≤ 4.9 served as the control group. Weight, body mass index (BMI), SUA, liver function, renal function, blood pressure, lipid profiles, and glycemic parameters were measured. Results . A total of 158 patients (101 men and 57 women) with complete data were analyzed in this study. 127 patients were identified as OSAHS. Among the 127 patients with OSAHS, 56 (44.1%), 37 (29.1%), and 34 (26.8%) had mild, moderate, and severe OSAHS, respectively. Correlation analyses showed that the SUA level was significantly related to the apnea-hypopnea index (AHI) (r = 0.194, p = 0.016 ). The level of SUA was significantly higher among OSAHS patients compared to the control group (control group:333.14 ± 80.52   μ mol/L, mild group:345.50 ± 90.27   μ mol/L, moderate group:363.59 ± 134.26   μ mol/L, and severe group:428.37 ± 123.58   μ mol/L andp = 0.029 ). Multivariable logistic regression analyses showed that SUA was the independent risk factor for OSAHS (OR: 1.006, 95% CI: 1.001-1.011, p = 0.020 ). Conclusions . The SUA level is significantly associated with the severity of OSAHS and should be controlled when managing OSAHS.